Cyclosporine A improves pregnancy outcomes in women with recurrent pregnancy loss and elevated Th1/Th2 ratio. Issue 10 (28th March 2019) - Azizi, Ramyar; Ahmadi, Majid; Danaii, Shahla; Abdollahi‐Fard, Sedigheh; Mosapour, Parisa; Eghbal‐Fard, Shadi; Dolati, Sanam; Kamrani, Amin; Rahnama, Badrossadat; Mehdizadeh, Amir; Jadidi‐Niaragh, Farhad; Yousefi, Bahman; et al.
Abstract: Recurrent pregnancy loss (RPL) is a one of the most common obstetrical complications. Since, the successful pregnancy occurs in T helper 2 (Th2)‐dominant situation and since, Th1 type immunity is related to pregnancy failure, we investigated the effects of cyclosporine on Th1 and Th2 cells in RPL women. Totally, 76 RPL patients (38 women as treated group and 38 as control group) were included in this study. Flow cytometry was utilized to analyze the frequency of Th1 and Th2 in blood samples. Also, real‐time polymerase chain reaction was carried out to assess the messenger RNA (mRNA) expression of transcription factors and enzyme‐linked immunosorbent assay was used to evaluate Th1 and Th2 related cytokines. Significant decrease in Th1 frequency ( p  = 0.0004), Th1/Th2 ratio ( p  < 0.0001), T‐bet mRNA expression ( p  < 0.0001), interferon‐γ ( p =  0.0007), and tumor necrosis factor α ( p  = 0.0002) secretion level were observed in cyclosporine group. Moreover, significant increase in Th2 frequency ( p  < 0.0001), mRNA expression of GATA binding protein 3 ( p  = 0.0001), and interleukin 10 secretion level ( p  = 0.0027) was also evident in treated group. At the end of the investigation, 31 (81.5%) patients in cyclosporine‐treated group had successful childbirth when compared with 16 (42.1%) women in control group ( p  = 0.0001). Given this, cyclosporine treatment for RPL patients with elevated Th1/Th2 ratio can result in improved pregnancy outcome. Abstract : Recurrent pregnancy loss (RPL) is a one of the most complications of pregnancy. T helper 1 (Th1) and Th2 cells play significant roles in immune allograft rejection or tolerance. One of the poor predictive factor for fertility outcome is enhanced natural killer (NK) cell and Th1 cells percentage. Successful pregnancy occurs in Th2‐dominant situation. Cyclosporine decreases the number of Th1 cells, capable to make a shift toward Th2 type responses and improves pregnancy outcome. Cyclosporine decreases the number of Th1 cells, capable to make a shift toward Th2 type responses and improves pregnancy outcome.